Integrated thematic geological mapping of the Atlantic Margin of Iberia. - Terrinha, Pedro (2020)
This paper synthesizes the geology of the Atlantic Margin off the coast of Iberia and surrounding Abyssal Plains using published thematic mapping freely downloadable from EMODNET-Geology portal at different scales. Selected information was chosen in order to highlight mineral occurrences and natural hazards overlaid on geological and morphological maps. Altogether, this information is published and interpreted here for the first time; nevertheless this exercise can be carried out by anyone interested and allows different visualizations of geological objects. Cross-correlations of geological objects and processes can easily arise. Because all of the information (each piece of data and metadata) in the EMODNET-Geology portal has bibliographic references associated, readers are able to find the original source of information. It is shown that clicking in and out of layers of information (that cannot be found all together in a single scientific paper) allows quick cross-correlation using the EMODNET Geology thematic portal. This allows a free, versatile and quick way of cross-correlating geological objects and processes in vast marine areas and their comparison with onshore geology